Effect of metatarsophalangeal joint position on the reliability of the tangential sesamoid view in determining sesamoid position - EROL, BÜLENT (AMER ORTHOPAEDIC FOOT & ANKLE SOC, INC, 2005)
Background. Lateral displacement of the sesamoids of the first toe relative to the metatarsal head is a common finding in hallux valgus deformity. Several methods have been described for quantifying the amount of subluxation from anteroposterior radiographs but a tangential sesamoid radiograph has been determined to be the best view to evaluate sesamoid displacement. Method. We evaluated the sesamoid position at different angles of the first metatarsophalangeal (MTP) joint to determine the effect of first MTP joint dorsiflexion on sesamoid position when tangential sesamoid view radiographs are made. Sesamoid positions of 22 feet with hallux valgus were graded from the short axis computed tomography (CT) images obtained with the MTP joint in 0, 35, and 70 degrees of dorsiflexion. Results: Approximation of the sesamoids to reduction was apparent as dorsiflexion of the first MTP joint increased. Conclusion: Different dorsiflexion degrees of the first MTP joint when tangential sesamoid radiographs are made modulate the position of the sesamoids and may lead to misclassification on grading.
Keywords: hallux valgus; reduction; sesamoid; tangential view; HALLUX-VALGUS; GREAT TOE; ROTATION